Evaluating forcings in an ensemble of paleo-climate models - Muri, H (2009)
This thesis presents the initial results from climateprediction.net's paleo-experiments. A grand ensemble of paleo-climate models was successfully designed and executed using this distributed computing approach. The physical parameters, initial conditions and boundary conditions were perturbed in two sets of experiments distributed to the general public. The paleo - focus period is the mid-Holocene, i.e. ~6000 years before present, due to its relative climatic stability and the abundance of geological evidence. Attempting to simulate climates that were substantially different from today provides an opportunity to evaluate model skill. A set of robust 6kyBP climatological features were established to benchmark the climate model against in order to assess the model’s abilities. Two experiments were distributed: in the first experiment the boundary conditions in the 6kyBP models took on the standard Paleoclimate Modelling Intercomparison Project (PMIP) values with altered orbital configuration as the main forcing on the climate. In a second experiment the local boundary conditions in Eastern North America (ENA) were also perturbed in the 6kyBP models to include an expanded Hudson Bay and land ice. The results highlight strengths and weaknesses in the model and stresses the importance of high quality paleo-observations. The models simulate the broad-scale features of the mid-Holocene climate reasonably well, though the model performance decreases when the benchmarks are inspected more closely. A relationship between the climate sensitivity, i.e. the equilibrium temperature response to doubling of pre-industrial CO2 concentrations, and the 6kyBP East Asian monsoonal moisture budget is found. This provides a climate sensitivity range of 2.5-6.1°C. The ENA boundary condition experiment concludes that the perturbations brought the climate models to a closer agreement with the geological records. A sensitivity experiment perturbing the North African vegetation cover emphasises the importance of vegetation feedbacks in relation to the 6kyBP northwards expansion of the monsoon.